Simulation of turbulent pipe flow with guided steady suction (blow) - Лунис, М. (Proceedings of National Aviation University, 1999)
Considered is the turbulent flow in a pipe with guided steady mass exchange through a porous wall. The proposed approach by Kinny and Sperrow is generalized for the cases of suction (blow) in the direction different from the normal to the main flow. For closure of equation we use Movtchan turbulent viscosity model. The solution is made by digital method. Besides the results received for the normal mass exchange given is the rated data about the influence of suction (blow) flow angle on velocity shape and friction coefficient